(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2009)
The sodium aluminium disulphate NaAl(SO4)2 has been obtained after calcinations at 300 Â°C of NaAl(SO4)2.12H2O alum. The structure of this compound has been refined from powder Â Â Â Â Â Â X-ray diffraction data using the Rietveld method. This compound crystallises in trigonal system Â Â Â Â Â Â P 3 2 1 with the following parameters: a = 4.749(12) Ã…, c = 8.314 (4) Ã… (Z = 1). Â The final refinement led to RF = 6.3 %, RB = 4.12 %. In the proposed model the sulfate ions is in disorder between two nonequivalent crystallographic sites with probabilities p1/p2= 0.30/70. The atomic arrangement of NaAl(SO4)2 is characterised by two different alternating layers parallel to (001): the first layer is composed of corner-linked AlO6 octhahedra and SO4 tetrahedra, the second layer is built from monovalent Na+ .Â